Modeling of cooling and heat conduction in permanent mold casting process - M. Ahmadein (Elsevier, 2022)
Motivated by the need to understand the heat transfer process in permanent mold casting, the heat conduction problem in the casting and the mold is modeled as transient one-dimensional heat flow in a double-layer cylinder with radial interfacial heat flux to emulate the cooling process of the casting. The cylinder is cooled down by dissipating heat to surrounding by convection. Green's function method, which obtained by separation of variables technique, is used to obtain a closed form solution of temperature distribution. The results of the derived analytical expressions are verified with numerical results of finite-element analysis and the published experimental results. The simulations are performed for different casting/mold materials with diversified thermo-physical properties to figure out the relationship between those properties and heat transfer process. The analytical results are justified by their good agreement with both of numerical and experimental results and its time efficiency in computation which offers advantages in potential real-time application to casting process monitoring. The mean absolute percentage error between the obtained temperatures using the developed analytical model and the measured ones was 14.5% and 2.4% for the casting and mold, respectively.